Murabahah Financing at BMT-UGT Nusantara Capem Kencong Based on PSAK 102 - Cahyani, Winda Nur; Nastiti, Ari Sita; Yuliarti , Norita Citra (West Science Accounting and Finance, 2025)
Financing is funding to support planned investments, either done by yourself or by others. This study aims to determine the application of murabahah conformity at BMT UGT Nusantara Capem Kencong with PSAK 102. This type of research is a qualitative descriptive approach research. Qualitative research is research on research that is descriptive in nature and tends to use analysis. This research was conducted at BMT-UGT Nusantara Capem Kencong located at Jalan Krakatau, Pondok Waluh, Kencong, Jember Regency, East Java. The research period was carried out from July to September 2024. The results of this study are the murabahah financing process at BMT-UGT Nusantara Capem Kencong in its implementation, BMT-UGT Nusantara Capem Kencong as a seller that meets customer needs and increases profits according to the agreement between BMT-UGT Nusantara Capem Kencong and customers. BMT-UGT Nusantara Capem Kencong informs customers about the acquisition price of the goods. The accounting treatment of murabahah at BMT-UGT Nusantara Capem Kencong is not fully in accordance with PSAK 102, because BMT-UGT Nusantara Capem Kencong does not impose any fines, considering that customers still find it difficult to pay installments.